Stimulation for Fine Motor Development of Children Through The Active Role of Parents in Palang Sub-district, Tuban - Wahyuningsih Triana Nugraheni; Teresia Retna Puspitadewi; Binti Yunariyah (Alliance oh Health Activists (AloHA), 2019)
The purpose of this research is to determine the provision of stimulation the fine motor development of children aged 4-5 years through the role of active parents in Palang Sub-district, Tuban. The population of this research was all the parents who have children aged 4-5 years in the kindergarten in Palang Sub-district, Tuban, with population size of 300 people. The sample size were 169 respondents. The sample were selected by using proportionate stratified random sampling. The independent variable was the role of parents in stimulation and the dependent variable was the fine motor development of children. Data of the role of parents were collected by using questionnaires and data of fine motor development were collected by using KPSP (development pre-sceening questionnaire). The data were analyzed by logistic regression test. The role of the parents as the model with p-value of 0.662, gives the opportunity to learn with p-value of 0.211; give the opportunity to practice with p-value of 0.222, motivation with p-value of 0.650 and guidance with p-value of 0.063. The 5 variation of the role of parents had no significant effect on the stimulation of smooth motor development of children aged 4-5 years. Keywords: role of the parents, stimulation, fine motor development